Mark Rein•Hagen’s Foundational Influence on 21st Century Vampiric Media - Konzack, Lars (Academic Quarter | Akademisk kvarter, 2015)
Mark Rein•Hagen’s role-playing game Vampire: The Masquerade, set in the World of Darkness shared universe, is foundational to the 21st Century vampire. We aim to, through the cultural analysis of how ideas have been transferred from this role-playing game to other media, clearly demonstrate Mark Rein•Hagen’s cultural historical significance.